Capacity and Level of Services for Signalized Intersections under Mix Traffic Conditions- A Global Scenario - Juremalani, Jayesh Rameshbhai; Chauhan, Dr. Krupesh A. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Saturation flow rate and control delay are very important parameters for the calculation of capacity and level of service at signalized at grade intersections. While many methods are currently available to estimate the saturation flow rates and delays incurred at intersection approaches, very little research has been conducted to assess the consistency of these estimates as they are less suitable under mix traffic conditions.This paper is divided into two parts. First saturation flow rate is discussed and various modifications which are made by various researches in the developing countries to match as far as possible the theoretical values obtained from the models with the real field values have been discussed one by one. In the second part delay is at intersections is explained in details along with modification suggested.